Analisis Keputusan Wisatawan Berkunjung Ke Objek Wisata Tilanga - Arah Pratiwi Topang; Isak Pasulu; Abedneigo. C. Rambulangi (Universitas Kristen Indonesia Toraja, 2023)
The problem of this research is how tourists decide to visit the Tilanga' tourist attraction. The types of data used are primary and secondary data with data collection techniques through observation and interviews with managers and visitors so that the data collected is truly accurate according to the researcher's needs. This research uses qualitative methods, data obtained from interviews and observations. The results of this research show that the respondents' decision to visit the Tilanga' tourist attraction was because the attraction of this object was able to make visitors come to the Tilanga' tourist attraction, such as the clear water, the atmosphere at one with nature, and even the Masapi that was there was able to attract tourists to visit.